Inhibition of MPO (Myeloperoxidase) Attenuates Endothelial Dysfunction in Mouse Models of Vascular Inflammation and Atherosclerosis. Issue 7 (July 2019) - Cheng, David; Talib, Jihan; Stanley, Christopher P.; Rashid, Imran; Michaëlsson, Erik; Lindstedt, Eva-Lotte; Croft, Kevin D.; Kettle, Anthony J.; Maghzal, Ghassan J.; Stocker, Roland
Abstract : Objective—: Inflammation-driven endothelial dysfunction initiates and contributes to the progression of atherosclerosis, and MPO (myeloperoxidase) has been implicated as a potential culprit. On release by circulating phagocytes, MPO is thought to contribute to endothelial dysfunction by limiting NO bioavailability via formation of reactive oxidants including hypochlorous acid. However, it remains largely untested whether specific pharmacological inhibition of MPO attenuates endothelial dysfunction. We, therefore, tested the ability of a mechanism-based MPO inhibitor, AZM198, to inhibit endothelial dysfunction in models of vascular inflammation. Approach and Results—: Three models of inflammation were used: femoral cuff, the tandem stenosis model of plaque rupture in Apoe −/− mice, and C57BL/6J mice fed a high-fat, high-carbohydrate diet as a model of insulin resistance. Endothelial dysfunction was observed in all 3 models, and oral administration of AZM198 significantly improved endothelial function in the femoral cuff and tandem stenosis models only. Improvement in endothelial function was associated with decreased arterial MPO activity, determined by the in vivo conversion of hydroethidine to 2-chloroethidium, without affecting circulating inflammatory cytokines or arterial MPO content. Mechanistic studies in Mpo −/− mice confirmed the contribution of MPO to endothelial dysfunction and revealed oxidation of sGC (soluble guanylyl cyclase) as the underlying cause of the observed limited NO bioavailability. Conclusions—: Pharmacological inhibition of MPO is a potential strategy to limit endothelial dysfunction in vascular inflammation. Abstract : Supplemental Digital Content is available in the text.